ANALISIS PENERAPAN PENDIDIKAN MULTIBUDAYA DI SEKOLAH DASAR: SEBUAH KAJIAN SYSTEMATIC LITERATURE REVIEW - Weni Yulastri; Muhtadi; Sesmuliastuti; Sri Zulmarni; Desi Novita; Nurul Mutiara (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Indonesia is a country with a high level of sociocultural diversity, which on the one hand is a national treasure, but on the other hand has the potential to trigger social conflict and acts of intolerance in the school environment. This study aims to identify, evaluate, and interpret the impacts and challenges of implementing multicultural education in elementary schools. The method used in this study is a literature study with a Systematic Literature Review (SLR) approach to reputable articles published within the last five years (2021–2026). The results of the analysis indicate that the implementation of multicultural education in elementary schools has a significant positive impact, such as building students' awareness of respect for differences, instilling values ​​​​of tolerance and empathy, and creating a safe and inclusive learning environment. However, the implementation of this approach still faces real challenges in the field, which include limited educator competence in managing diverse classes, minimal training in multiculturalism concepts, a curriculum that is not yet fully integrated, and educational policies that are not yet adaptive in terms of funding and provision of diversity teaching materials. Therefore, the success of multicultural education requires a transformation of values ​​from mere theory or annual celebrations to real, everyday experiences, supported by improved teacher competency and more comprehensive curriculum integration.